THE PROCESS OF INSTITUTIONALIZATION AND REGULATION OF MARTIAL ARTS IN BRAZIL - Pedro Gabriel Gil Parizotto; Allan Fernando Zardo da Silva; Carlos Herold Junior; Fernando Augusto Starepravo (Universidade Estadual do Oeste do Paraná, 2017)
The present work aimed to describe the historical process of the regulation of Japanese martial arts in Brazil and its relation with Physical Education. The foundation in the educational scope defines the teaching of the combats comprehensively seeking an approximation of the theme with the Physical Education in the scholar environment. We conclude that the institutionalization of martial arts in Brazil has not yet occurred in fact, remanding still, an ongoing process, the desire for this institutionalization occurs in the search for the legitimation of martial practice.